Intelligent Aging Home Control Method and System for Internet of Things Emotion Recognition - Wu, Xu; Zhang, Qian (Frontiers in Psychology, 2022)
In order to solve a series of pension problems caused by aging, based on the emotion recognition of the Internet of things, the control method and system research of smart home are proposed. This paper makes a detailed analysis and Research on the necessity, feasibility and how to realize speech emotion recognition technology in smart family, introduces the definition and classification of emotion, and puts forward five main emotions to be recognized in speech emotion recognition based on smart family environment. Then, based on this, it analyzes the acquisition methods of emotional speech data, On this premise, this paper discusses and analyzes the related problems of voice data acquisition in smart home, such as the voice characteristics and acquisition methods, puts forward three rules for voice text design, and determines the relatively suitable hybrid recording acquisition method applied in smart home environment, At the same time, the design and establishment process of intelligent family emotional speech database are described in detail. The related problems of feature extraction in speech emotion recognition are studied. Starting from the definition of feature extraction, this paper expounds the necessity of feature extraction in the process of recognition, and analyzes the characteristics of speech signal. For the specific environment of smart family, the speech signal required to be processed needs to be close to the auditory characteristics of human ears, and the speech signal contains enough information. Finally, the Mel frequency cepstrum coefficient (MFCC) is selected as the feature parameter applied in this paper, and the extraction process of MFCC is introduced in detail.